Detection of Proteinuria by Colorimetric Method and Correlation with Disease Severity in Patients Dengue - Acivrida Mega Charisma; Elis Anita Farida; Farida Anwari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Severe dengue virus infection often causes proteinuria through several mechanisms, such as leakage of plasma proteins caused by higher protein filtering in the kidneys. The condition of proteinuria in patients with dengue shock syndrome will affect the management, prognosis, and mortality of patients with dengue virus infection. The objectives of this study were to determine the presence of protein in urine samples in patients in which IgG/IgM dengue was detected, to determine the presence of protein in urine samples in patients without dengue infection, and to determine the relationship between proteinuria in dengue patients and the degree of disease severity. The study was conducted in March-June 2020 at the Clinical Laboratory and Inpatient Clinic of Vita Medika Kepung, Kediri Regency. The method used was the consecutive sampling technique. The minimum sample size was 100 respondents with criteria for suspected dengue infection, onset fever > 4 days, age > 2 years, and no indication of other infectious diseases (blood and urine), divided into two groups, group with positive dengue infection and non-dengue group. The results showed that proteinuria was detected in 26% of respondents, secondary dengue infection and positive serological test of IgG, IgM only IgG were detected in 24 (92.3%) respondents and positive IgG and IgM were found in 2 (7.7%) respondents, this was shown by the p-value = 0.000 in the Chi-Square test with a Prevalence Ratio (PR) value of 11,987. In addition, Chi-Square test results indicated that a higher urine protein/albumin led to more severe disease, with p-value = 0.012 and 0.025 (p <0.05) and PR values of 3.333 and 2.800. The results of this study concluded that there was a close relationship between high levels of protein/albumin in the urine with the degree of disease severity in patients with dengue infection. In addition, an increase in urine protein/albumin levels is always followed by a decrease in serum protein/albumin levels.